Implementation of Box Jump Innovation Training towards Improving Volleyball Smash Ability in Extracurricular Activities of SMP Negeri Sidoharjo - Pajarwati, Neni; Suhdy, Muhammad; Syafutra, Wawan (STKIP Paasundan Press, 2024)
Ability smash on participants Sidoharjo State Middle School education Still low and lacking A variation in exercises that can increase ability smash it . For overcome problem the with method given A treatment exercise Innovation box jump For increase ability smash his . Research This For know implementation exercise innovation box jump to improvement ability volleyball smash in activities extracurricular Sidoharjo State Junior High School . Research This use method Quantitative with type experiment and use design one-group pretest-posttest design with given treatment as many as 16 meetings . The population used in study This is all over participant students who follow Volleyball extracurricular activities at Sidoharjo State Middle School . Data collection techniques sample namely total sampling, then sample used all over participant students who follow activity activity volleyball extracurricular activities consisting of 20 students . Data collection techniques in study This use test Smash Ability Research This use technique data analysis used with count A mean value , standard deviation , and mean difference test ( t-test ) . from results study show that study This there is implementation exercise box jump innovation against improvement volleyball smash ability in activities extracurricular Sidoharjo State Junior High School . So you can seen from results t- value count from exercise box jump innovation against smash ability of 12.80 and obtained mark from t- table with degrees his freedom is 20-2 (dk = 18) at the level significance α = 0.05 is 1.73. This is means t- count = 12.80 > t- table = 1.73. So it can be concluded that ' There is Implementation of Box Jump Innovation Training Against Improvement Volleyball Smash Ability In Activities Sidoharjo State Middle School Extracurricular Activities ' can accepted the truth.